2014
DOI: 10.1111/jicd.12139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of periodontal status on oral health‐related quality of life among police personnel in Virajpet, India

Abstract: In the present study, there was an association between OHRQoL and periodontal status among police personnel in Virajpet, Coorg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Studies also evaluated the impact of oral conditions over OHRQoL, classified according to exposure to one or more oral conditions, dental caries, gingivitis, periodontal disease, edentulism, malocclusion, dental fluorosis, bruxism and prosthetic need. Studies related to dental caries are ( n = 20) [ 38 , 41 , 43 , 48 , 50 , 51 , 53 , 55 , 57 – 62 , 66 , 68 , 69 , 73 , 75 , 77 ], Gingivitis ( n = 6) [ 38 , 42 , 51 , 58 , 69 , 79 ], Periodontal Disease assessed by Loss of Attachment ( n = 9) [ 42 , 43 , 47 , 48 , 51 , 67 , 69 , 72 , 74 ], Periodontal Disease assessed by Community Periodontal Index ( n = 10) [ 42 , 43 , 46 – 48 , 51 , 57 , 67 , 69 , 74 ], malocclusion ( n = 10) [ 38 , 43 , 49 , 54 , 56 , 58 – 60 , 64 , 80 ], Dental fluorosis ( n = 2) [ 43 , 70 ], Bruxism ( n = 2) [ 52 , 71 ], Functional Edentulism/Edentulism ( n = 9) [ 45 , 57 , 58 , 65 , 66 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies also evaluated the impact of oral conditions over OHRQoL, classified according to exposure to one or more oral conditions, dental caries, gingivitis, periodontal disease, edentulism, malocclusion, dental fluorosis, bruxism and prosthetic need. Studies related to dental caries are ( n = 20) [ 38 , 41 , 43 , 48 , 50 , 51 , 53 , 55 , 57 – 62 , 66 , 68 , 69 , 73 , 75 , 77 ], Gingivitis ( n = 6) [ 38 , 42 , 51 , 58 , 69 , 79 ], Periodontal Disease assessed by Loss of Attachment ( n = 9) [ 42 , 43 , 47 , 48 , 51 , 67 , 69 , 72 , 74 ], Periodontal Disease assessed by Community Periodontal Index ( n = 10) [ 42 , 43 , 46 – 48 , 51 , 57 , 67 , 69 , 74 ], malocclusion ( n = 10) [ 38 , 43 , 49 , 54 , 56 , 58 – 60 , 64 , 80 ], Dental fluorosis ( n = 2) [ 43 , 70 ], Bruxism ( n = 2) [ 52 , 71 ], Functional Edentulism/Edentulism ( n = 9) [ 45 , 57 , 58 , 65 , 66 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found there is a significant association between individuals with periodontal disease and OHRQoL [ 48 , 74 ] and another study by Nagarajappa et al 2015 denied the association ( P =0.687) [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 El personal policial, es un grupo de profesionales que tienen de forma global, un entorno de trabajo diferente, con servicio de 24 horas y a menudo, están expuestos a un gran esfuerzo físico y estrés mental, lo cual repercute en su salud bucal y en efecto en su calidad de vida. 10 Es posible que este personal, no utilice los servicios de salud brindadas por el estado; siendo una de las causas más importantes el factor tiempo, de modo que, muchos optan por la atención particular, generando así, gastos adicionales no previstos, lo que incrementa el malestar del personal policial. En el 2020, Ocwia y col. 13 analizaron los comportamientos sobre salud bucal, en 400 adultos, de 18 años a más, de la comunidad de Nebbi, Uganda, a través de un estudio transversal.…”
Section: Materiales Y Métodosunclassified